Radiological Simultaneous Portohepatic Vein Embolization (RASPE) Before Major Hepatectomy: A Better Way to Optimize Liver Hypertrophy Compared to Portal Vein Embolization. Issue 2 (August 2020) - Laurent, Christophe; Fernandez, Benjamin; Marichez, Arthur; Adam, Jean-Philippe; Papadopoulos, Panteleimon; Lapuyade, Bruno; Chiche, Laurence
Abstract : Objective: The aim of this retrospective study was to compare portal vein embolization (PVE) and radiologica simultaneous portohepatic vein embolization (RASPE) for future liver remnant (FLR) growth in terms of feasibility, safety, and efficacy. Summary of Background Data: After portal vein embolization (PVE), 15% of patients remain ineligible for hepatic resection due to insufficient hypertrophy of the FLR. RASPE has been proposed to induce FLR growth. Materials and Methods: Between 2016 and 2018, 73 patients were included in the study. RASPE was proposed for patients with a ratio of FLR to total liver volume (FLR/TLV) of <25% (RASPE group). This group was compared to patients who underwent PVE for a FLR/TLV <30% (PVE group). Patients in the 2 groups were matched for age, sex, type of tumor, and number of chemotherapy treatments. FLR was assessed by computed tomography before and 4 weeks after the procedure. Results: The technical success rate in both groups was 100%. Morbidity post-embolization, and the time between embolization and surgery were similar between the groups. In the PVE group, the FLR/TLV ratio before embolization was 31.03% (range: 18.33%–38.95%) versus 22.91% (range: 16.55–32.15) in the RASPE group ( P < 0.0001). Four weeks after the procedure, the liver volume increased by 28.98% (range: 9.31%–61.23%) in the PVE group and by 61.18% (range: 23.18%–201.56%) in the RASPE group ( P < 0.0001). Seven patients in the PVE group, but none in the RASPE group, had postoperative liver failure ( P = 0.012). Conclusions: RASPE can be considered as "radiological associating liver partition and portal vein ligation for staged hepatectomy." RASPE induced safe and profound growth of the FLR and was more efficient than PVE. RASPE also allowed for extended hepatectomy with less risk of post-operative liver failure. Abstract : Supplemental Digital Content is available in the text